In-Vitro Pharmacological Profile f Partially Purified Leaves of Alseodaphne Perakensis - Okechukwu, Patrick Nwabueze (2005)
Alseodaphne perakensis (AP) is a moderately sized tree that is widely distributed throughout Peninsular Malaysia. There are no reports of this tree in traditional folk medicine although tests have shown its leaves are rich in alkaloids. Initial experimental work carried out on this species led to the isolation of a major compound N-methy1-2,3,6-trimethoxymorphinandien-7-onea,n alkaloid with a morphinandienone skeleton which is similar in structure with Omethylflavinanthine; and a minor trimethoxymorphinandien-7-one-N-oxide. Another compound 7-hydroxy-2,3,6- trimethoxy phenantherenel has also been isolated. All these three compounds isolated from AP have no reported biological activity. However, the alkaloid Omethylflavinanthine has been previously isolated from other plants and its analgesic properties has been reported by other researchers. polar alkaloid N-methyl-2,3,6- In this study, the crude methanol extract (CMLE) and semi-pure alkaloids were extracted by steeping the air-dried leaves of AP in methanol for 48hrs. The solvent methanol containing CMLE were evaporated using the rotary evaporator at 45OC leaving a blackish viscous CMLE. The alkaloid in CMLE were extracted using the sulphuric acid, sodium carbonate, and methylene chloride (DCM) to obtain DCM 'A' and DCM 'B' and de-alkaloid fractions (residue after alkaloid extraction). Alkaloid test (Meyer's reagent) done on these extracts CMLE and DCM 'A' and DCM 'B' fractions confirmed the presences of alkaloid;' the residue after alkaloid extraction tested negative for alkaloid. These extracts CMLE, DCM 'A' and DCM 'B' from the leaves of AP were tested on stimulated and unstimulated guinea pig ileum (GPI), rat vas deferentia (RVD) and mouse vas deferentia (MVD) preparations. The CMLE (100 p1,O. 1 g/ml) inhibited the electrically induced twitches on the GPI preparation. On its own, CMLE has no effect on the unstimulated GPI. Contractions induced by histamine and acetylcholine on the unstimulated GPI preparation were antagonised in a non-competitive manner by CMLE (100 p1 0.1 g/ml). DCM 'A' (100 pl0.1 glml) was also found to inhibit the electrically induced twitches on the GPI preparation. On its own, DCM 'A' had no effect on the unstimulated GPI. DCM 'A' also antagonised the contraction induced by histamine and acetylcholine on the unstimulated GPI in a non-competitive manner. The CMLE (1 00 p1 0.1 g/ml) inhibited the electrically induced twitches on the RVD preparation. On its own, CMLE had no effect on the unstimulated RVD. Contractions induced by phenylepherine on the unstimulated RVD preparation was antagonised in a competitive manner by CMLE (100 p1 0.1 glml). Like CMLE, DCM 'A' (100 yl 0.1 glml) inhibited the electrically induced twitches on the RVD preparation. On its own, DCM 'A' had no effect on the unstimulated RVD. DCM 'A' also antagonized contractions induced by phenylepherine on the unstimulated RVD. Like phenylepherine antagonist phentolamine, both CMLE and DCM 'A' competitively inhibited contraction induced by phenylepherine on RVD. CMLE and DCM'A' inhibited the electrically induced twitch on the stimulated MVD; they did not have any effect on the unstimulated MVD. The inhibition by CMLE and DCM'A' fraction on the stimulated MVD was reversed by naloxone. DCM 'B' fraction did not have any effect on the stimulated GPI, RVD and MVD preparation. It also did not have any effect on the unstimulated RVD and MVD, however, DCM 'B' fraction induced contractions in a dose dependent manner on the unstimulated GPI. These contractions were antagonised competitively by mepyramine. The dealkaloid (dAK) fractions did not show any physiological effect on the stimulated and unstimulated GPI, stimulated and unstimulated RVD and stimulated and unstimulated MVD. CMLE and DCM 'A' fractions from the leaves of AP seem to possess; antihistaminergic, antimuscarinic, antiadrenergic, morphine-like activity. DCM 'B' fraction exhibited histaminergic activity.